A JURIDICAL ANALYSIS OF EMPLOYEE CREDIT RIGHTS IN THE BANKRUPTCY OF PT. KERTAS LECES (PERSERO) - Alfons Manuel P. M. Napitupulu (jfpublisher, 2025)
This study examines the juridical position of employee wage claims in the bankruptcy of PT. Kertas Leces (Persero) to determine how Indonesian law reconciles creditor equality with constitutional principles of social justice. Using a normative juridical method, the research analyzes primary legal materials, including Law No. 37 of 2004 on Bankruptcy, Law No. 11 of 2020 on Job Creation, and Constitutional Court Decision No. 67/PUU-XI/2013, supported by comparative references from the International Labour Organization (ILO), UNCITRAL, and the World Bank. The findings reveal that the Constitutional Court transformed wage protection from a statutory privilege into a constitutional entitlement, asserting that employees’ wages represent part of the right to life and human dignity guaranteed by the 1945 Constitution. This interpretation was subsequently codified in Article 95 of the Job Creation Law, which prioritizes the payment of wages above all other unsecured debts. The PT. Kertas Leces case demonstrates the practical application of this principle, establishing employees as preferred creditors within the bankruptcy distribution hierarchy. Comparative analysis shows that Indonesia’s approach aligns with international standards advocating limited wage priority as a legitimate social-policy exception to pari passu. The study concludes that the prioritization of wage claims embodies a balance of justice, legal certainty, and utility, transforming Indonesia’s bankruptcy framework into a moral and constitutional instrument for protecting human dignity and promoting equitable economic governance.